Dissecting galactic bulges in space and time – I. The importance of early formation scenarios versus secular evolution. Issue 3 (28th November 2014) - Seidel, M. K.; Cacho, R.; Ruiz-Lara, T.; Falcón-Barroso, J.; Pérez, I.; Sánchez-Blázquez, P.; Vogt, F. P. A.; Ness, M.; Freeman, K.; Aniyan, S.
Abstract: The details of bulge formation via collapse, mergers, secular processes or their interplay remain unresolved. To start answering this question and quantify the importance of distinct mechanisms, we mapped a sample of three galactic bulges using data from the integral field spectrograph WiFeS on the ANU's 2.3-m telescope in Siding Spring Observatory. Its high-resolution gratings ( R  ∼ 7000) allow us to present a detailed kinematic and stellar population analysis of their inner structures with classical and novel techniques. The comparison of those techniques calls for the necessity of inversion algorithms in order to understand complex substructures and separate populations. We use line-strength indices to derive single stellar population equivalent ages and metallicities. Additionally, we use full spectral fitting methods, here the code steckmap, to extract their star formation histories. The high quality of our data allows us to study the 2D distribution of different stellar populations (i.e. young, intermediate and old). We can identify their dominant populations based on these age-discriminated 2D light and mass contribution. In all galactic bulges studied, at least 50 per cent of the stellar mass already existed 12 Gyr ago, more than currently predicted by simulations. A younger component (age between ∼1 and ∼8 Gyr) is also prominent and its present day distribution seems to be affected much more strongly by morphological structures, especially bars, than the older one. This in-depth analysis of the three bulges supports the notion of increasing complexity in their evolution, likely to be found in numerous bulge structures if studied at this level of detail, which cannot be achieved by mergers alone and require a non-negligible contribution of secular evolution.